Transcrições das Lendas Amazônicas de Waldemar Henrique para canto e violão: uma abordagem prática e teórica - Anderson dos Reis dos Santos (2017)
The present works main objective is to transcribe the Lendas Amazônicas (Legends from the Amazon), a set of nine songs originally for voice and piano by Waldemar Henrique, for guitar and voice. Relations between the composer and the guitar were searched in his biography and different performance possibilities for his work were found different from those originally created by the composer. Transcription in understood in this work as the reestablishment of a text by changing is original medium or instrument. Transcription here is also related to the concept of poetic translation as done by authors such as Barbeitas, Dutra, Szendy, Jarrel and Unes. For such purposes, musical and extra-musical references were used in order to create the transcriptions, departing from the textual content of the legends described in the songs. The transcriptions of the nine songs were elaborated with the support by the methodology developed by Daniel Wolff (1998) and by the personal experience as a guitarist and accompanist and presenting the main techniques and thoughts applied. Since the transcription process also requires an editorial process, some considerations regarding our editions were presented, explaining our choice for the term transcription.